Strategi Keluarga Muslim Dalam Pendidikan Islam Terhadap Remaja Di Era Modern Kelas IX SMP Al-Azhar Syifa Budi Cibinong Kelurahan Sukahati Kecamatan Cibinong Kabupaten Bogor - Aini Indah Dwi Cahyani Adam; Syahidah Rena; Pahrurraji; Fajar Syarif (Al-Ishlah: Jurnal Pendidikan Islam, 2021)
This paper proposes to describe the strategy of Muslim families in Islamic education for adolescents in the modern era of class IX SMP Al-Azhar Syifa Budi Cibinong. This research is qualitative (field research), descriptive analytical research method, sociological and psychological approach. Primary research sources, namely documentation and interviews of school principals, students, and their guardians. The secondary sources are obtained from relevant journal articles and books. Data analysis used the theory of Milles and Huberman, namely data collection, reduction, presentation, drawing conclusions, and data validation. The results of the study indicate that the family plays an important role in instilling Islamic education for adolescents in the modern era, namely: 1. Educational challenges and opportunities: Free flow of external culture and information, youth character formation, science and technology advancement, and health 2. The role of parents, namely: Making common rules, providing appropriate technology to children, sending children to religious-based schools, and assisting teenagers using smartphones. The methods are coaching, habituation, dialogue, example, discipline, promises, threats, ibrah, and mau'idzah. 3. The supporting factors are the existence of school facilities, the active role of parents, and technological facilities, while the inhibiting factors for family education are a negative social environment, negative children's personalities, and parents who are busy working.